PEMILIKAN DAN PENGUASAAN TANAH (DESA DI JAWA TIMUR) - Wijayati, Putri Agus (Forum Ilmu Sosial, 2008)
Land was the most valuable thing for the javanese. Through the property in land, the ones could bemeasure by his social structure as well as capital matters. Feodalism and Dutch colonial rules in ruralJava had shaped many kind of ownership and property in land. The argument of the article was to servesome description of ownership and property in land of Besuki residence, East Java. Since 1743, thisteritory was occupied by the Dutch colonial after released from the Mataram imperial. The colonial hadadapted the former concept of the traditional ownership and property in land. It mentioned that any kindthat layed in the land, was belong to the emperor. Mackenzie by his report for Land Tenure Commisionstate that the Emperor of Java was the lad owner. The ownership and property in land of Besuki residenceshape of some kind, there are; individual-land, communal-land, state-land, and private-land.Keywords : Feodalism, ownership, property in land